Comparative Analysis of Physical Maps of Four Bacillus subtilis (natto) Genomes - Qiu, Dongru (American Society for Microbiology, 2004)
The complete SfiI and I-CeuI physical maps of four Bacillus subtilis (natto) strains, which were previously isolated as natto (fermented soybean) starters, were constructed to elucidate the genome structure. Not only the similarity in genome size and organization but also the microheterogeneity of the gene context was revealed. No large-scale genome rearrangements among the four strains were indicated by mapping of the genes, including 10 rRNA operons (rrn) and relevant genes required for natto production, to the loci corresponding to those of the B. subtilis strain Marburg 168. However, restriction fragment length polymorphism and the presence or absence of strain-specific DNA sequences, such as the prophages SPβ, skin element, and PBSX, as well as the insertion element IS4Bsu1, could be used to identify one of these strains as a Marburg type and the other three strains as natto types. The genome structure and gene heterogeneity were also consistent with the type of indigenous plasmids harbored by the strains.